Biophysical contexture of coastal biofilm-sediments varies heterogeneously and seasonally at the centimeter scale across the bed-water interface - Chen, Xindi; Kang, Yanyan; Zhang, Qian; Jin, Chuang; Zhao, Kun (Frontiers in Marine Science, 2023)
Coastal sediments filter and accumulate organic and inorganic materials from the terrestrial and marine environment, and thus provide a high diversity of microbial niches. However, sediment-based analyses typically examine bulk samples and seldom consider variation at a scale relevant to changes in environmental conditions, due to the lack of mid-long term field data which can cover both the seasonal and sediment depth variations. In this study, microbial production and bacterial community structure were determined together with grain parameters over 10 months of intertidal silty sands on Jiangsu Coast, China. We demonstrated that the microbiological effects did not merely present on the surface, but greatly varied and stratified in both physical and biological contexture within the top 4 cm layer. Bacterial community structure showed a clear vertical variation with higher operational taxonomic unit (OTU) numbers at 1~2 cm depth than in the top 2 mm, probably because of the decreasing disturbance by hydrodynamic forces. However, the microbial production rates and metabolic activities, represented by the production of extracellular polymeric substances (EPS), were always higher in the top. Seasonal changes were strongly reflected in the vertical patterns of EPS but could not explain the variation across sites. The overall EPS secretion in spring and summer was generally at high level than that in autumn and winter, with the maximum value of 5~6 times higher. Interestingly, the stratification of biological and physical properties followed a fixed relationship, where with the decrease of the grain size D50, the EPS content increased exponentially, and this relationship was independent of temporal or spatial variation. Despite the significant seasonal variation of microbial activity and sedimentary grain size individually, the basic function between EPS content and D50 however did not alter. Filling these knowledge gaps will not only help to decipher the fate of grain-biofilm aggregates and organic matter burial under global changes, but also provide field evidence for the development of sediment transport models as well as blue carbon models incorporating microbial processes.